Prolonged grief and posttraumatic stress in parents who lost a child in a road traffic accident: A latent class analysis - I. van Dijk; P.A. Boelen; J. de Keijser; L. Reitsma; L.I.M. Lenferink (Journal of Affective Disorders Reports, 2025)
Background: The traumatic loss of a child in a road traffic accident (RTA) can lead to mental health issues in parents, such as symptoms of prolonged grief (PG) and posttraumatic stress (PTS). Latent class analysis (LCA) provides insights into different responses to such losses. Methods: Using LCA, 148 parents that were bereaved at least twelve months earlier, were categorized into latent classes based on similar response patterns. Associations between class membership and sociodemographic and loss-related variables and self-directed anger were examined. Results: Two symptom patterns emerged: a 'High PG/Moderate PTS' pattern (73.2 %) and a 'Moderate-High PG/Low PTS' pattern (26.8 %). Mothers and those with more self-directed anger were more likely to present with the first symptom pattern. Limitations: Inclusion of parents undergoing therapy for clinically relevant symptoms, small sample size, no differentiation between parents of minor and adult children, and including only four PTS symptoms are limitations that may have influenced the identified symptom patterns. Conclusions: Parents who lost a child in a RTA seem at risk for developing psychological symptoms, with PG being more predominant than PTS. The study highlights the possible value of addressing modifiable factors such as self-directed anger in therapeutic interventions for PG and PTS after traumatic loss of a child.